STUDENT LEARNING STYLES IN THE DEVELOPMENT OF MULTISENSORY WORKTEXTS FOR FILIPINO LANGUAGE INSTRUCTION - Ambas, Hien; Feliciano, Divina (International Journal of Arts, Sciences and Education, 2025)
This study focuses on student learning styles in the development of multisensory worktexts for Filipino language instruction. The research employed an R&D (Research and Development) design. Two groups of students, 10-Gold and 10-Sapphire, were identified using complete enumeration sampling as respondents to determine their learning styles, which served as the basis for the development of the multisensory worktext. The study also assessed the level of acceptance of the developed worktext by both the students and the teachers. Based on the survey results identifying learning styles, it was discovered that a significant number of students preferred a visual learning style. The developed worktext was also highly accepted by both the students and the teachers. The multisensory worktext was also highly accepted by experts who evaluated its validity. The study further revealed that there was no significant correlation between learning styles and student acceptance of the worktext’s quality. There was no significant relationship between the three learning styles and the developed worktext, except for the kinesthetic style. The kinesthetic learners showed slightly lower acceptance of the worktext’s format and a lower acceptance of its originality, particularly when combined with an auditory learning style. The level of acceptance of the developed worktext was significantly higher among students than among teachers, due to the teachers’ lower acceptance of the clarity and originality of the multisensory worktext. Therefore, the teacher’s resourcefulness and creativity in preparing teaching materials such as multisensory worktexts and their use in instruction have a positive impact on students’ academic learning and performance.